Rekonstruksi Pertanggungjawaban Hukum Penyelenggara Platform E-Commerce terhadap Perlindungan Konsumen dalam Transaksi Negosiasi Digital - Berliandya Hasanuddin; sudiyana (Jurnal Hukum Lex Generalis, 2026)
The rapid growth of e-commerce in Indonesia has introduced digital negotiation transactions that lack adequate legal regulation. This study analyzes the legal liability construction of e-commerce platform operators toward consumer protection in digital negotiation transactions under Indonesian positive law and formulates an ideal reconstruction model. Using a normative juridical method, the study finds that existing legal instruments the Consumer Protection Law, the Electronic Information and Transactions Law and the Government Regulation on Electronic Commerce fail to explicitly regulate platform liability in digital negotiation, creating a normative vacuum that structurally disadvantages consumers. Reconstruction requires integrative regulatory reform, institutional strengthening, minimum technical standards and sustained consumer legal literacy enhancement.